Encyclopedia of Electrochemistry 2006
DOI: 10.1002/9783527610426.bard072406
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemistry of Mercury

Abstract: The sections in this article are Double‐layer Properties of Hg /Water Interface Potential of Zero Charge Surface Charge Density and Capacitive Current Experimental and Theoretical Studies of the Hg /Water Interface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 192 publications
(144 reference statements)
0
3
0
Order By: Relevance
“…The relation between I pa vs. square root of scan rate was linear, which indicated that the electrode reaction was diffusioncontrolled (Bard and Faulkner, 2001). However, at lower scan rates of up to 20 mV/s, the I pa showed only single oxidation peak, which may be due to a slower process, as the reaction occurs in one step: Hg 2+ + 2e− = Hg 0 (Orlik and Galus, 2007). The po-Gr/PEDOT:PSS-modified GCE showed a linear response for various Hg 2+ concentrations from 0.3 to 1.6 mM (R 2 = 0.997) ( Figure 8B).…”
Section: Linear Sweep Voltammetrymentioning
confidence: 95%
See 1 more Smart Citation
“…The relation between I pa vs. square root of scan rate was linear, which indicated that the electrode reaction was diffusioncontrolled (Bard and Faulkner, 2001). However, at lower scan rates of up to 20 mV/s, the I pa showed only single oxidation peak, which may be due to a slower process, as the reaction occurs in one step: Hg 2+ + 2e− = Hg 0 (Orlik and Galus, 2007). The po-Gr/PEDOT:PSS-modified GCE showed a linear response for various Hg 2+ concentrations from 0.3 to 1.6 mM (R 2 = 0.997) ( Figure 8B).…”
Section: Linear Sweep Voltammetrymentioning
confidence: 95%
“…These peaks are attributed to two welldefined one-electron steps, according to the two-step equation: Hg 2+ + e − = Hg + + e − = Hg 0 (Orlik and Galus, 2007). The presence of po-Gr on both bare GCE and PEDOT:PSS-modified GCE improved the peak current (I pa ) compared to that in the absence of po-Gr.…”
Section: Linear Sweep Voltammetrymentioning
confidence: 99%
“…The electrooxidation of Co­(I) to Co­(II) is fast and occurs at −1.369 V. At about −0.238 V, the reduction peaks corresponding to Co­(III)/Co­(II) reduction processes are observed. The subsequent reduction peak of Co­(II) → Co­(III) transformation is recorded at −0.980 V. The Cu­(MIPM) 2 Cl 2 complex shows two quasi-reversible peaks recorded at E 1/2 = 0.289 V and E 1/2 = −0.806 V corresponding to the electrochemical processes of Cu­(III)/Cu­(II) and Cu­(II)/Cu­(I), respectively. In the case of mercury complex (Hg­(MIPM)­Cl 2 ), the voltammogram shows two well-defined redox systems at E 1/2 = −0.006 V and E 1/2 = −0.334 V. These peaks are attributed to two one-electron transfers of the couples Hg II+ /Hg I+ and Hg I+ /Hg 0 , respectively. , One irreversible cathodic peak was recorded at −1.511 V in the voltammogram of Zn­(MIPM) 2 Cl 2 . This peak corresponds to the reduction process of Zn­(II) to Zn(0).…”
Section: Resultsmentioning
confidence: 99%